Gharials of beas - Department of forests & wildlife preservation, government of Punjab (Chandigarh Department of forests & wildlife preservation, 2022)
Gharial (Gavialis gangeticus) is a critically endangered, non-aggressive crocodilian species locally known as "sansar". It is named after its bulbous inverted pot-like growth ("ghara") in adult males. This fish-eating crocodilian species can be easily identified from other crocodiles for its elongated snout with about 106-110 sharp visible inter-locking teeth along the length of the snout.
Keywords: Crocodile